Psychological Support for Individuals Experiencing Acute Trauma (Based on Experience Working with Victims of a Terrorist Attack at Crocus City Hall) - I.V. Vachkov; E.I. Viryasova; O.S. Melenteva; M.A. Panfilova (Клиническая и специальная психология)
The paper presents a description of methods and techniques for providing psychological assistance to people in the acute stage of trauma, using specific cases of psychological counseling of clients in the days following a terrorist attack at Crocus City Hall as an example. The main research objectives were to identify characteristic signs of acute trauma and propose possible ways to provide psychological support for adults, children, and adolescents. The article analyzes domestic and international literature on the psychological consequences of terrorist attacks, considering the main mental disorders and symptoms associated with the trauma of being a witness, as well as methods and techniques for working with individuals who have experienced mental trauma. Five specific cases of people seeking psychological help are described in the article. Based on personal experience, the authors suggest a possible algorithm for dealing with trauma in witnesses and describe some effective techniques: eye movement desensitization and reprocessing (EMDR), breathing exercises, and imagotherapeutic techniques using a metaphor (“Resource (safe) place”, as well as techniques aimed at muscle relaxation and self-regulation.